The last stand [book with audioplayer] - Eady, Antwan ([Library Ideas, LLC], 2024)
A little boy is excited to work alongside his Papa as they collect eggs, plums, peppers and pumpkins to sell at their stand in the farmer's market, but when Papa cannot make it to the stand, his community gathers around him, with dishes made of his own produce.